Efficiency of ursodeoxycholic acid in the frameworks of minimization of hepatotoxic potential of eradication therapy of Helicobacter pylori infection - D. N. Andreev; I. V. Mayev; D. T. Dicheva; L. G. Bektemirova (Лечащий Врач)
The article presents results of the study whose objective was efficiency assessment for application of ursodeoxycholic acid in the frameworks of minimization of hepatotoxic action of antibacterial drugs included in the composition of classical triple scheme of eradication therapy of Helicobacter pylori infection.